Juvenile crime and justice - Chambliss, William J.; Sage Publications (Thousand Oaks, Calif. : SAGE, 2011)
Presents arguments both in favor of and opposed to various treatments, programs, and punishments, examining issues such as youth curfews, juveniles in adult courts, legal representation for juveniles, juvenile boot camps, group homes, and out-of-home placement.
Age of responsibility -- Alternative schools -- At-risk youth -- Boot camps -- Curfews -- Death penalty for juvenile offenders -- Group homes -- Juvenile detention facilities -- Juvenile gangs and delinquency -- Juvenile offenders in adult courts -- Juveniles in adult correctional facilities -- Legal representation -- Out-of-home placement -- Parental responsibility laws -- Racial disparities -- Scared straight programs -- School violence -- Sentencing options -- Serious and violent juvenile offenders -- Treatment and rehabilitation.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Juvenile delinquency; Crime; Law enforcement; Corrections; Criminal justice, Administration of; Délinquance juvénile.; Lois -- Application; Services correctionnels; SOCIAL SCIENCE -- Criminology; Corrections; Crime; Criminal justice, Administration of; Juvenile delinquency; Law enforcement; Ungdomsbrottslighet -- Förenta staterna; Reference works; Reference works; Ouvrages de référence.